Evaluation of anaesthetic techniques for caesarean - Banerjee, Alaka; Sarkar, Dhrubajyoti; Bhadra, Banasree (International Journal of Research in Medical Sciences, 2018)
Background: The anaesthetic technique to be used in Caesarean section is determined according to factors such as urgency, presence of coexisting health problems, preference of patient and preference and experience of the anaesthetist and surgeon. Methods: This is a retrospective study of all the caesarean deliveries that occurred in the period between 1st Jan 2010 to 31st Dec 2017 in the department of obstetrics and Gynaecology in Silchar Medical College. The anaesthesia techniques used for caesarean sections were evaluated in this study. Anaesthesia methods were recorded as general anaesthesia (GA) and regional anaesthesia (RA), and RA was classified into spinal anaesthesia (SA), epidural anaesthesia (EA) and combined spinal epidural anaesthesia (CSEA) subgroups. Results: During the study period a total of 75685 patients delivered and 25805 patients had undergone caesarean section. The caesarean section rate at the institution comes to be around 34.1%. Among the indications, it was observed that foetal distress (32.8%) was the commonest cause followed by post caesarean pregnancy (26.76%). The majority of the CS (75.6%) were done as an emergency procedure. Regional anaesthesia was the most frequently used method both in emergency (92.87%) and elective caesarean section (84.21%). SA was the commonest used RA (89.2%). Conclusions: In recent years, the rate of regional anaesthesia administration in caesarean section is gradually increasing, and the spinal anaesthesia technique is the mostly preferred regional anaesthesia. There is need to explore the use of the other forms of regional anaesthesia also.